THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS OF PREGNANT WOMEN AND FETALGROWATH: A LITERATURE REVIEW - Puspita, Deri; Tampubolon, Berliana; Imran Saputra Surbakti; Tusiyanti, Sarni; Bakara, Sri Muliana Putri (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Pregnancy is a crucial period that determines maternal health and fetal growth. Energy and nutrient needs increase significantly to support the mother’s physical changes and the development of fetal organs. Nutritional problems such as Chronic Energy Deficiency (CED) with a Mid-Upper Arm Circumference (MUAC) <23.5 cm, anemia, and low nutritional knowledge are still common. These conditions carry the risk of complications, stunted fetal growth, low birth weight (LBW), and even stunting, which have long-term impacts. Objectives: To examine the relationship between nutritional status of pregnant women and fetal growth and pregnancy outcomes.(Maslikhah, Prajayanti and Baroroh, 2023) Methods: This study employed a systematic literature review. Sources were searched through Google Scholar and health journal databases, covering publication years 2019–2025. A total of 13 relevant articles were selected and analyzed, encompassing cross-sectional, cohort, and experimental designs. The variables studied included MUAC, hemoglobin levels, nutritional intake, and fetal growth and birth weight parameters. Result: Maternal nutritional status is significantly related to fetal growth. Mothers with a mid-birth weight (MULA) ≥ 23.5 cm have a 2–3 times lower risk of giving birth to a low-birth-weight (LBW) baby. Conversely, CED and anemia increase the risk of fetal growth restriction and stunting by up to 3.7 times. Providing supplemental food, iron supplements, and nutrition education have been shown to be effective in improving maternal nutritional status. Conclusions: The better the mother’s nutritional status, the more optimal the fetus’s growth. Regular monitoring, balanced nutrition, and counseling from early pregnancy are essential to ensure a successful pregnancy outcome.